Impact of Exchange Rate on Stock Market - Suriani, Seri; Kumar, M. Dileep; Jamil, Farhan; Muneer, Saqib (International Journal of Economics and Financial Issues, 2015)
The exchange rate and stock market are the two fundamental financial markets in the world. These two markets are playing key role in an international business all over the world. It is necessary to understand the relationship between the both markets so that the investors may be able to invest in a better way by taking the minimum risk. This paper investigates the relationship between the stock market and exchange market of Pakistan. KSE-100 index is used as a substitute of Stock Prices while currency rate of Pak Rupee against US Dollar (Rs/US) is taken for exchange rate exposure. The data is on monthly basis and the time period is from January 2004 to December 2009. The findings of the study indicate that there is no relationship exists between exchange rate and stock price and both the variables are independent of each other. Keywords: Fundamental Financial Markets, Exchange Rates, Stock Market JEL Classifications: F31, O16